Methods for individualising factor VIII dosing in prophylaxis. (August 2014) - Ar, Muhlis Cem; Vaide, Ines; Berntorp, Erik; Björkman, Sven
Abstract: Haemophilia A is a sex‐linked disorder characterised chiefly by recurrent, spontaneous joint and muscle bleedings resulting from deficiency of factor VIII (FVIII). Recurrent joint bleeds result in haemophilic arthropathy. Unless treated with factor replacement therapy, many patients with severe haemophilia become disabled. The first clinical evidence favouring prophylaxis originated from the studies in Sweden and the Netherlands in the 1960s. Later on, it was shown that prophylaxis could prevent arthropathy, if started early in life, or slow its progression in adults with established arthropathy. The optimal dosing of FVIII in long‐term prophylaxis has still not been determined, and there is growing evidence that the dose and frequency of FVIII should be individualised. We conducted a systematic search of PubMed to identify all relevant articles on FVIII prophylaxis in severe haemophilia A. We focused on articles with detailed information about individualisation of prophylaxis. Long‐term prophylaxis in haemophilia was introduced in Sweden in the late 1950s. However, standard prophylactic regimens may not be appropriate for all patients with severe haemophilia. Factors such as age, joint status, co‐morbidities and differences in pharmacokinetics lead to interindividual variation in factor requirement. Dose tailoring of FVIII by clinical outcome was first described in 1994. Since then, several dose‐finding studies questioned the necessity to maintain preinfusion levels of FVIII above 1%. Individualising prophylaxis by dose tailoring is now recommended. Each country should adopt policies for individualising prophylaxis in patients with severe haemophilia. This would lead to a better distribution of the available source of factor concentrates.